The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7860/jcdr/2022/57699.17041
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Nursing Interns during COVID-19 in Taif University, Saudi Arabia: A Qualitative Study

Abstract: Introduction: Coronavirus Disease-2019 (COVID-19) has affected nursing staff and students mentally and physically due to their role in the frontline fighting the virus. However, data on the effect of COVID-19 on nursing students are limited and there have been no studies about Saudi nursing intern experience during this crisis. Aim: To explore the impact of COVID-19 pandemic on nursing students during their interns at hospitals and how they dealt with the COVID-19 pandemic. Materials and Methods: A qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Furthermore, the study found that nursing students lacking preparation and orientation programs had difficulty adjusting to the clinical environment, affecting their overall clinical experience. These findings align with the results of several studies conducted (Alharbi & Alhosis, 2019 ; Alkarani, 2022 ) that investigated the clinical learning experiences of nursing students in Saudi Arabia. Alkarani ( 2022 ) conducted a qualitative study exploring the experience of internship students.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, the study found that nursing students lacking preparation and orientation programs had difficulty adjusting to the clinical environment, affecting their overall clinical experience. These findings align with the results of several studies conducted (Alharbi & Alhosis, 2019 ; Alkarani, 2022 ) that investigated the clinical learning experiences of nursing students in Saudi Arabia. Alkarani ( 2022 ) conducted a qualitative study exploring the experience of internship students.…”
Section: Discussionsupporting
confidence: 90%
“…These findings align with the results of several studies conducted (Alharbi & Alhosis, 2019 ; Alkarani, 2022 ) that investigated the clinical learning experiences of nursing students in Saudi Arabia. Alkarani ( 2022 ) conducted a qualitative study exploring the experience of internship students. The study yielded similar results to the current research, indicating that students felt lost when they lacked communication with others and had ambiguous roles.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nursing internship program in Saudi Arabia is a hospital‐based practice for one‐year permits graduates to demonstrate their abilities in real‐life and under regulated conditions through research and education programs (Alkarani, 2022). Yet, the experience gained from nursing clinical education is different from internship programs.…”
Section: Introductionmentioning
confidence: 99%